THE EFFECT OF INTERPERSONAL THERAPY ON DEPRESSION AND ANXIETY AMONG ADOLESCENT INMATES IN ACEH: A PRE-EXPERIMENTAL STUDY - Miftahurrahmi; Syarifah, Rauzatul Jannah; Febriana, Dara (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
Juvenile inmates are highly vulnerable to mental health disorders, particularly depression and anxiety. Factors such as the prison environment, limited social support, and restricted access to mental health services contribute to this vulnerability. If left untreated, these conditions can adversely impact their psychological well-being and rehabilitation process. Interpersonal Therapy is a psychotherapeutic approach focusing on interpersonal relationships, proven effective in treating affective disorders among adolescents. This study aimed to assess the effectiveness of Interpersonal Therapy in reducing depression and anxiety among juvenile inmates at the Banda Aceh Juvenile Correctional Institution. A Pre - experimental one-group pre-test and post-test design was employed. A total of 33 participants were recruited using purposive sampling, based on power analysis (power 0.80, effect size 0.70, α = 0.05). The intervention consisted of five sessions of Interpersonal Therapy. Data were collected using demographic questionnaires, the Beck Depression Inventory-II (BDI-II) to measure depression, and the Beck Anxiety Inventory (BAI) to assess anxiety levels. The Wilcoxon Signed-Rank Test revealed a significant effect of Interpersonal Therapy on reducing depression (Z = -3.764; p < 0.001) and a non-significant trend in reducing anxiety (Z = -1.732; p = 0.083). Before the intervention, most respondents had moderate depression (60.6%) and mild anxiety (66.7%). After the intervention, 45.5% of participants experienced minimal depression, while mild anxiety increased to 87.9%. The mean depression score decreased from 20.94 to 13.79, and the anxiety score from 17.27 to 13.58. Interpersonal Therapy was effective in reducing depression and contributed to improvements in anxiety among juvenile inmates. This therapy can be used as a non-pharmacological approach in psychiatric nursing to support adolescents mental well-being in correctional settings